التَّناظر في القرآن الكريم: تأصيلٌ وتطبيق - سليمان الدقور; أيمن عيد الرواجفة (International Institute of Islamic Thought, 2019)
تتحدَّد فكرة التَّناظر في القرآن الكريم في أنَّ بناء القرآن في سوره وآياته قائم على نظام واضح تتناظر فيه السُّور القرآنية لتكون كل سورة في النِّصف الأوَّل مُناظِرة لسورة أُخرى في النصف الثاني، بحسب عدد السُّور، وتتناظر فيه الآيات في السُّورة الواحدة بالطريقة نفسها. والبحث في هذا التَّناظر القرآني وعناصره مهمة نبيلة لتدبُّر كتاب الله عَزَّ وجَلَّ، وتفيد في إثبات إعجاز هذا الكتاب، وتناسق ترتيبه، ومناسبات سوره وآياته. والتَّناظر بين سور القرآن الكريم، وله نموذجان، هما: تناظر السُّورتين في تسلسل بدء السُّورة مع بدء السُّورة الأُخرى، وتناظر السُّورتين في تسلسل بدء السُّورة مع ختام السُّورة الأُخرى. والتَّناظر في السُّورة الواحدة، له نموذجان، هما: التَّناظر بين آيات السُّورة الواحدة، والتَّناظر بين موضوعات السُّورة ومقاطعها. ويظهر التَّناظر في هذين النموذجين الأخيرين بشكلين من التَّناظر، هما: تسلسل تناظر البدء مع البدء، وتسلسل تناظر البدء مع الختام. The idea of symmetry in the Holy Quran is determined by the fact that the construction of the Qur'an in its surah is based on a clear symmetry in which the Qur'anic chapters in the first half of the Quran are symmetrical to chapters in the second half, in terms of the number of chapters according to the number of chapters, The verses of one chapter are also symmetrical in the same way. Investigating of such arrangements would be a noble mission that offers deep understanding of the Holy Qur'an, leads to clear interpretation, helps to prove its miracles, and consistency of its order and structure of chapters and verses. Idea of symmetry in chapters has two examples:, symmetry is found in there  beginnings, and in the beginnings of one chapter and end of the other. Symmetry among verses of a certain chapter has also to examples; symmetry in its verses and symmetry in its subjects and parts. These two kinds of symmetry would be clear beginning of a chapter and the beginning of another, and in the beginning and the end.